Intercultural approaches in multicultural counseling and pastoral care: Exploring interaction and transformation - Kim, Miyoung (Pastoral psychology, 2025)
As globalization and neoliberalism drive increased international migration, the need for counseling and pastoral care for culturally diverse migrants is expanding. This study analyzes counseling experiences with a Korean Mongolian multicultural family using a case study methodology, exploring how intercultural interventions manifest in the counseling process. The findings reveal that intercultural approaches facilitate not only problem resolution but also mutual transformation. The researcher focused on exploring the client’s personal, social, and cultural needs through cultural assessment and pastoral theological reflection, emphasizing practical intercultural interventions. This study proposes a pastoral circle method for intercultural intervention, outlining four stages: reflection, revelation, response, and restoration. Future research should further examine the applicability and effectiveness of intercultural counseling with migrants from diverse cultural backgrounds.